Pap smear screening in antenatal women: an opportunistic way to save life - Siddiqui, Sana; Rehman, Suhailur; Bano, Imam; Arif, Sayeedul H. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2021)
Background: Cancer cervix is the most common genital tract malignancy encountered in developing countries. In India, first visit to the gynaecologist for most women is during pregnancy and it may be the only visit. Hence, prenatal care offers an excellent opportunity to implement cervical screening in patients of young age, especially in women who do not seek routine health care. Therefore, this study was conducted to know the prevalence of abnormal Pap smear among the ante-natal women and to evaluate the result in relation to various risk factors. Methods: Cross sectional observational study conducted on 425 ante-natal women attending the antenatal clinic using questioner addressing various socio-demographic variables. Measures of central tendency calculated and result was tabulated by using chi-square test. Results: Maximum number of cases in our study was NILM i.e.314 (74%) followed by 68 cases of Candida (16%), 30 cases of Bacterial vaginosis (7.1%) and 10 cases of Trichomonas vaginalis (2.4%). Only 3 cases of abnormal Pap smear was reported i.e. 2 of ASCUS and 1 of LSIL. Thus, prevalence of abnormal Pap smear was 0.7%. Conclusions: In country like India where organised screening programme are not available, as well as the awareness and uptake of available services by the target population is also poor; screening in pregnancy is worthwhile and may be a viable option to reduce the burden of cervical carcinoma.